Predicting the Significance of Trust, Service Quality, and Values for Customer Satisfaction - Ayu Anggraini, Rika (Research of Business and Management, 2024)
The purpose of this study is to ascertain, partially simultaneously, the effects of customer value, trust, and service quality on customer satisfaction. Customers of the PT. Bank Central Asia, Tbk Kelapa Gading Villa Branch, comprising 835 individuals overall, were the subjects of the study, with 167 samples, or 20% of the entire population, being included in the sample. This study's sampling strategy combines nonprobability sampling with accidental sampling, meaning that samples are taken by the researcher when he happens to come across them. Quantitative data are the kind required for this study. In this study, information obtained directly from respondents and shown on a Likert scale is referred to as quantitative data. Questionnaires, interviews, and observation are some of the data collection methods employed. Multiple regression statistics are applied. The study's findings demonstrate a strong correlation between customer satisfaction and service quality, as well as between customer value and customer contentment. Customer happiness is significantly impacted by the independent variables, which are service quality, trust, and customer value, all at the same time. This has management ramifications for recognizing client value, fostering trust, monitoring, and assessment, as well as for increasing service quality